2012
DOI: 10.1371/journal.ppat.1002697
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus Infection of Naïve B Cells In Vitro Frequently Selects Clones with Mutated Immunoglobulin Genotypes: Implications for Virus Biology

Abstract: Epstein-Barr virus (EBV), a lymphomagenic human herpesvirus, colonises the host through polyclonal B cell-growth-transforming infections yet establishes persistence only in IgD+ CD27+ non-switched memory (NSM) and IgD− CD27+ switched memory (SM) B cells, not in IgD+ CD27− naïve (N) cells. How this selectivity is achieved remains poorly understood. Here we show that purified N, NSM and SM cell preparations are equally transformable in vitro to lymphoblastoid cells lines (LCLs) that, despite upregulating the act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
56
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 79 publications
(85 reference statements)
4
56
1
Order By: Relevance
“…This idea is supported by the observation that EBV reactivation is often delayed until 2 to 3 months after transplant, concomitant with the onset of lymphopoiesis. Whether EBV drives the differentiation of emerging naive B cells, either by germinal center transit 1 or by inducing a memory phenotype via a GC-independent pathway, 54 or through the direct infection of memory B cells, 55 remains to be tested. For personal use only.…”
Section: Discussionmentioning
confidence: 99%
“…This idea is supported by the observation that EBV reactivation is often delayed until 2 to 3 months after transplant, concomitant with the onset of lymphopoiesis. Whether EBV drives the differentiation of emerging naive B cells, either by germinal center transit 1 or by inducing a memory phenotype via a GC-independent pathway, 54 or through the direct infection of memory B cells, 55 remains to be tested. For personal use only.…”
Section: Discussionmentioning
confidence: 99%
“…*p , 0.05, **p , 0.01. T cell signals are needed to alter the Ig phenotype of the parental population (naive or non-switched memory) (39). Furthermore, previous studies found that all B cell subsets irrespective of Ig class and memory status have the same ability to be infected in vitro and that the proliferation rate of infected switched memory B cells was equal to that of naive cells (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…T cell signals are needed to alter the Ig phenotype of the parental population (naive or non-switched memory) (39). Furthermore, previous studies found that all B cell subsets irrespective of Ig class and memory status have the same ability to be infected in vitro and that the proliferation rate of infected switched memory B cells was equal to that of naive cells (39,40). Thus, the emergence of a large IgD 2 CD27 + B cell population in EBV-infected cultures of older children likely represents acquisition of a memory phenotype by infected naive cells along with class-switching/downregulation of IgD, rather than preferential expansion of pre-existing CD27 + B cells.…”
Section: Discussionmentioning
confidence: 99%
“…Virus titrations were carried out by quantitative PCR (qPCR) as described previously (59). Primary B cells were positively selected from apheresis cones (National Health Service Blood and Transplant [NHSBT], Birmingham, United Kingdom) by using CD19 Dynabeads (Invitrogen), followed by a detachment step and then assessment for purity as described elsewhere (60). Isolated resting B cells were incubated with virus preparations at a multiplicity of infection (MOI) of 100.…”
mentioning
confidence: 99%